1987
DOI: 10.3109/00016488709128282
|View full text |Cite
|
Sign up to set email alerts
|

Can Uvulopalatopharyngoplasty Be Harmful to Eustachian Tube Function?

Abstract: A study of the Eustachian tube, incorporating nasendoscopy, tympanometry and pressure swallow test was undertaken in patients undergoing uvulopalatopharyngoplasty. Marked negative middle ear pressure indicating impairment of tubal function was found during the first 7 postoperative days. In patients receiving antibiotic treatment the Eustachian tube dysfunction was significantly alleviated. This dysfunction is probably due to a postoperative infective inflammatory process in the tonsillar fossa. Antibiotic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It was designed to concentrate on the immediate E-tube function after surgery. Most studies have already established that there are immediate and marked MEP reductions that gradually recover [13][14][15][16][17][18][19]. In this study, three weeks after surgery, there were no specific complaints or physical examinations that were suggestive of E-tube dysfunction.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It was designed to concentrate on the immediate E-tube function after surgery. Most studies have already established that there are immediate and marked MEP reductions that gradually recover [13][14][15][16][17][18][19]. In this study, three weeks after surgery, there were no specific complaints or physical examinations that were suggestive of E-tube dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…Finkelstein et al [15] described that uvulopalatopharyngoplasty induced noticeable MEP reduction during the first 7 postoperative days. Marais and Armstrong [17] evaluated the long-term effect of laser-assisted uvulopalatoplasty on middle ear function, and found no significant differences in middle ear volume or pressure three months after surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Surgery for obstructive sleep apnea using Z‐palatopharyngoplasty has a transient effect on lowering middle ear pressures on postoperative day 3, with pressures returning to baseline on subsequent measurements 12. In patients undergoing uvulopalatopharyngoplasty, Finkelstein et al found marked negative middle ear pressure indicating impairment of tubal function during the first 7 postoperative days, which was alleviated with postoperative antibiotics 13…”
Section: Discussionmentioning
confidence: 99%
“…3 Negative pressure changes in the middle ear are observed due to edema in the nasopharynx following tonsillectomy but there aren't many studies to prove the same. 4,5 Tympanometry is indirectly used to determine the middle ear pressure changesboth pre operatively and post operatively. Though endoscopic assisted coblation technique of tonsillectomy and adenoidectomy is superior to curettage there is a paucity of literature to assess the effectiveness in measuring residual adenoid size and evaluate middle ear pressure by tympanometry which was carried out in our study.…”
Section: Introductionmentioning
confidence: 99%